Fifty million rising the new generation of working women transforming the Muslim world - Zahidi, Saadia (New York Nation Books, 2018)
In Fifty Million Rising, award-winning economist Saadia Zahidi illuminates this discreet but momentous revolution through the stories of the remarkable women who are at the forefront of this shift--a McDonald's worker in Pakistan who has climbed the ranks to manager; the founder of an online modest fashion startup in Indonesia; a widow in Cairo who runs a catering business with her daughter, against her son's wishes; and an executive in a Saudi corporation who is altering the culture of her workplace; among many others. These women are challenging familial and social conventions, as well as compelling businesses to cater to women as both workers and consumers. More importantly, they are gaining the economic power that will upend entrenched cultural norms, re-shape how women are viewed in the Muslim world and elsewhere, and change the mindset of the next generation.
Includes bibliographical references and index.
Keywords: Women--Employment--Islamic countries